Interaction Between Mesenchymal Stem Cells and Retinal Degenerative Microenvironment - Lin, Yu; Ren, Xiang; Chen, Yongjiang; Chen, Danian (Frontiers in Neuroscience, 2021)
Retinal degenerative diseases (RDDs) are a group of diseases contributing to irreversible vision loss with yet limited therapies. Over decades, innovative treatments involving the regeneration of degenerative cells and restoration of healthy retinal microenvironment have emerged, among which cell replacement strategies have caught considerable attention. Mesenchymal stem cells (MSCs) that are easy to harvest and with low immunogenicity are an ideal source for stem cell therapy and have been studied in plenty of degenerative diseases. MSCs can promote regeneration of degenerative retina by cell differentiation and facilitate the regain and maintenance of retinal homeostasis via trophic, anti-apoptotic, immunomodulation, and anti-inflammatory functions. On the other hand, the degenerated retinal microenvironment also plays a crucial role in the survival, differentiation, and biological activity of transplanted MSCs. In this review, we mainly discuss recent advances concerning the functions of MSCs in treating RDDs and their interactions with the retina.